Automatic presser-foot force control for industrial sewing machines - Carvalho, Helder (2012)
To develop and test control methods for real-time automatic presser-foot force control in industrial sewing machines. In this work, a closed-loop controller that controls presser-foot maximum vertical displacement is presented and compared to existing solutions that adjust force depending on sewing speed. Automatic force control can reduce problems such as stitch irregularity, stitch distortions and material damage, besides making material handling easier. Design/methodology/approach An electromagnetic force actuator was integrated in an industrial lockstitch machine. A computer-based control system was designed implementing either speed-variable force control, closed-loop control, or emulating a traditional constant-force system. Maximum presser-foot displacement values were measured and analysed in relevant sewing situations, and seam quality was assessed. Findings Constant-force control does not allow optimal force setting at all speeds. Speed-variable force control is an improvement, but requires empirical setting of the speed-force relation, not always assuring optimal operation. Closed-loop control adapts force to the requirement of each sewing situation more precisely. Sewing quality is good and material handling is eased. Research limitations/implications The actuator has to be optimised regarding response time and maximum force. Some aspects in the behaviour of the control system and actuator have to be further studied. Practical implications The proposed control system enables the automatic setting and adaptation of force to all sewing situations, making material handling easier at low speeds without compromising feeding performance at high speed. The closed-loop controller may be used as teach-in system for speed-dependent control. Originality/value This is the first prototype of a closed-loop control system for presser-foot force on a lockstitch sewing machine and the first comparative study of control methods for presser-foot force control.